A Review: Electrospun Nanofiber Materials for Lithium‐Sulfur Batteries. (28th August 2019) - Liu, Min; Deng, Nanping; Ju, Jingge; Fan, Lanlan; Wang, Liyuan; Li, Zongjie; Zhao, Huijuan; Yang, Guang; Kang, Weimin; Yan, Jing; Cheng, Bowen
Abstract: Lithium‐sulfur (Li‐S) batteries are in the spotlight because their outstanding theoretical specific energy is much higher than those of the commercial lithium ion (Li‐ion) batteries. Li‐S batteries are tough competitors for future‐developing energy storage in the fields of portable electronics and electric vehicles. However, the severe "shuttle effect" of the polysulfides and the serious damage of lithium dendrites are main factors blocking commercial production of Li‐S batteries. Owing to their superior nanostructure, electrospun nanofiber materials commonly show some unique characteristics that can simultaneously resolve these issues. So far, various novel cathodes, separators, and interlayers of electrospun nanofiber materials which are applied to resolve these challenges are researched. This review presents the fundamental research and technological development of multifarious electrospun nanofiber materials for Li‐S cells, including their processing methods, structures, morphology engineering, and electrochemical performance. Not only does the review article contain a summary of electrospun nanofiber materials in Li‐S batteries but also a proposal for designing electrospun nanofiber materials for Li‐S cells. These systematic discussions and proposed directions can enlighten thoughts and offer ways in the reasonable design of electrospun nanofiber materials for excellent Li‐S batteries in the near future. Abstract : Owing to the nanostructure, electrospun nanofiber materials commonly exhibit some unique features to address the issues associated with sulfur cathodes, separators, and interlayers in Li‐S batteries. This review presents the fundamental research and technological development of multifarious electrospun nanofiber materials for Li‐S batteries. An insightful perspective is outlined for future research in electrospun nanofiber materials of Li‐S batteries.